Models and Forms of Integration of Science and Islam - Adyaksa (Al-Abqori: Journal of Islamic Thought Studies, 2025)
This article discusses the relationship between science and religion in the context of Islam. Integration between the two disciplines has been an important part of the Islamic intellectual tradition, and this article highlights various models of integration, including the Islamization of science, Islamic scientism, convergence, and complementarity. Each model offers a different approach to combining science and religion, whether in research, education, or public policy. By combining empirical knowledge with spiritual values, this integration is expected to enrich Muslims' understanding of the universe and life, and strengthen their faith in God. Challenges and opportunities in this integration are also discussed, including differences in methodology and potential positive contributions to environmental sustainability and social welfare. This article emphasizes the importance of collaboration between scientists and religious scholars to create holistic solutions that benefit humanity as a whole.